Analytical assessment of physical characteristics, metabolic processes, and molecular investigations of selected wheat (Triticum spp.) cultivars - Dina H. M. Shehata; Mohamed M. El-Mahdy; Mohamed Ibrahim; Magda M. I. EL Araby; Somia S. El -Akkad; Faten Y. Ellmouni (BMC Plant Biology)
Abstract Background Wheat, a primary cereal crop, is crucial in addressing global food security. Understanding genetic diversity and conserving wheat germplasm is essential for developing cultivars resilient to climate change. This study investigates grain quality, nutritional profiles, and genetic diversity across a selection of Egyptian and internationally sourced wheat cultivars. Physical and chemical analyses were conducted to assess grain/flour quality, hardness, and micronutrient content. Genetic diversity was evaluated using protein profiling, SCoT markers, and rbcL chloroplast DNA barcoding, chosen for its highly conserved nature and proven utility in plant species identification and phylogenetic analysis, making it a reliable marker for assessing genetic relationships among wheat cultivars. The findings from this study revealed distinct patterns of genetic variation and highlight valuable traits within the germplasm, providing crucial information for developing wheat cultivars adapted to diverse climatic conditions. Results Physical and biochemical analyses revealed that two Egyptian cultivars, Sohag 5 and Misr 1, exhibited superior quality and nutritional value among the nine evaluated wheat cultivars. Both showed favorable physical properties (e.g., grain weight, falling number, gluten content). Sohag 5 was notably rich in carbohydrates, protein content, and essential minerals (zinc, calcium, magnesium), while Misr 1 also maintained healthy carbohydrate and gluten levels. Genetic diversity analysis, employing SDS-PAGE protein profiling and SCoT markers, effectively differentiated the wheat cultivars. These molecular markers consistently grouped the cultivars, generally distinguished between bread wheat and durum wheat varieties, and provided insights into the genetic relationships between Egyptian and imported lines. While the specific clustering patterns varied between marker types, particularly with rbcL sequences providing a distinct grouping since the rbcL chloroplast gene exhibited limited resolution for differentiating closely related cultivars. The combined genetic data confirmed significant diversity within the germplasm. Overall, the analysis identified two primary genetic groups among the cultivars, with Group I comprising seven diverse cultivars and Group II containing two distinct cultivars (Benisuif 6 and Sohag 5). Conclusions Overall, the investigated Egyptian wheat cultivars demonstrated competitive or superior performance in standard physical and nutritional parameters compared to the imported varieties, with Sohag 5 and Misr 1 notably excelling in grain quality and micronutrient content. The genetic diversity analysis, incorporating protein profiling, SCoT markers, and rbcL chloroplast DNA barcoding, effectively characterized the genetic landscape of the cultivars. A key finding was the consistent genetic distinction of specific Egyptian cultivars, notably Sohag 5 and Benisuif 6, which clustered uniquely, aligning with their classification as durum wheat varieties. This revealed genetic relationships, alongside the identified superior traits (e.g., in Sohag 5), provides valuable insights that can be strategically utilized in breeding programs to develop new wheat cultivars with enhanced quality and adaptability to diverse climatic conditions.